When does transitioning from family to professional management improve firm performance? - Chang, Sea‐Jin; Shim, Jungwook (Strategic Management Journal, 2015)
Using long‐term data on J apanese family firms, this study explores when the transition from family to professional management leads to better performance. In order to avoid endogeneity bias, we employ propensity score matching and difference‐in‐differences techniques. We find evidence that firms that transition from family to professional CEO s outperform those that maintain family leadership. This performance improvement is more pronounced when (1) families maintain high ownership control but leave no family legacy behind, (2) when the transition moves from non‐founder family managers to professionals, and (3) when professional managers graduated from elite universities . Copyright © 2014 John Wiley & Sons, Ltd.